Magnetic resonance imaging reveals therapeutic effects of interferon-beta on cytokine-induced reactivation of rat model of multiple sclerosis - Serres, S; Bristow, C; De Pablos, R; Merkler, D; Soto, MS; Sibson, N; Anthony, D (2013)
Interferon-β (IFN-β) drugs are considered to derive their beneficial effects on multiple sclerosis (MS) progression via their antiinflammatory properties, but the precise mechanism of action remains unclear. Here, we sought to discover how IFN-β impacts on inflammation-associated aggravation of MS-like lesions in rat. Animals with dormant focal experimental allergic encephalomyelitis (EAE) lesions were challenged intravenously with a replication-deficient adenovirus vector carrying interleukin (IL)-1β cDNA (AdIL-1β). Aggravation of inflammation and demyelination within the focal EAE lesion was observed after AdIL-1β injection with associated changes in tissue structure detected by diffusion and magnetization transfer imaging. Postgadolinium-DTPA T 1-weighted images revealed contrast enhancement in the ipsilateral meninges, indicating breakdown of the blood-cerebrospinal fluid barrier, and increased left/right regional cerebral blood volume ratio was also observed after AdIL-1β injection. To determine the role of IFN-β on reactivation of the EAE lesion, rats were treated with therapeutic doses of IFN-β and focal EAE lesions showed significantly reduced reactivation in response to systemic AdIL-1β injection. In conclusion, these findings indicate a central role for peripheral IL-1β expression in the mechanism of MS lesion reactivation and that the therapeutic effects of IFN-β may, at least in part, reflect suppression of the effects of peripheral inflammation on MS lesion pathogenesis. © 2013 ISCBFM All rights reserved.